2019
DOI: 10.1002/ajoc.201900328
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Palladium‐Catalyzed Suzuki‐Miyaura Cross‐Coupling of (Diborylmethyl)silanes with Alkenyl Bromides

Abstract: Herein, we report the development of a palladium‐catalyzed chemoselective cross‐coupling of (diborylmethyl)silanes with alkenyl bromides. The reaction shows broad scope with respect to alkenyl bromides and (diborylmethyl)silanes, affording a range of α‐silyl‐substituted allylic boronate esters in good‐to‐excellent yields. The practicality of the developed coupling reaction is demonstrated by the gram‐scale synthesis of α‐silyl‐substituted allylic boronate ester.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…[22] The same authors have reported a method for synthesizing various α-silyl-substituted allylic boronate esters through the palladium-catalyzed chemoselective coupling of (diborylmethyl)silanes with alkenyl bromides under mild conditions. [23] Borylsilyl-methanes can also be substituted with heteroatoms as Ge, Sn. [24] Shimizu et al, prepared [CH-(SnBu 3 )(Bpin)(SiMe 2 Ph)] (3) and generated the corresponding carbanion with LDA followed by germylation with Me 3 GeCl (Scheme 9a).…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] The same authors have reported a method for synthesizing various α-silyl-substituted allylic boronate esters through the palladium-catalyzed chemoselective coupling of (diborylmethyl)silanes with alkenyl bromides under mild conditions. [23] Borylsilyl-methanes can also be substituted with heteroatoms as Ge, Sn. [24] Shimizu et al, prepared [CH-(SnBu 3 )(Bpin)(SiMe 2 Ph)] (3) and generated the corresponding carbanion with LDA followed by germylation with Me 3 GeCl (Scheme 9a).…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…This methodology established the Pd(TFA) 2 as catalyst precursor of choice and NaOMe as base, requiring NaI as additive for quantitative conversion, although its role in the mechanism remains unclear (Scheme 8b) [22] . The same authors have reported a method for synthesizing various α‐silyl‐substituted allylic boronate esters through the palladium‐catalyzed chemoselective coupling of (diborylmethyl)silanes with alkenyl bromides under mild conditions [23] …”
Section: α‐Silicoboron Carbanionsmentioning
confidence: 99%
“…An early example of the catalytic synthesis of achiral α-boryl silanes was developed by Suginome, who used iridium-catalyzed C–H borylation of tetraalkylsilanes or ruthenium-catalyzed C–H silylation of methylboronic acid derivatives. A Pd-catalyzed cross-coupling of (diborylmethyl)­silanes was also developed recently to prepare racemic α-boryl silanes …”
Section: α-Boryl Silanesmentioning
confidence: 99%
“…A Pd-catalyzed cross-coupling of (diborylmethyl)silanes was also developed recently to prepare racemic α-boryl silanes. 80 The first catalytic approach to nonracemic α-boryl silanes was accomplished by the Yun group in 2012. 81 Through copper-catalyzed chemoselective double borylation of silylacetylenes 149, α,β-diborylalkyl silanes 150 were prepared with syn selectivity.…”
Section: α-Boryl Silanesmentioning
confidence: 99%
“…Significantly, the reaction shows very high regioselectivity when conjugated diene gem-diboryl (7aj) was subjected to the photoredox reaction conditions; the 1,2-addition product (6aj) was observed as the sole product in 41% yield (Scheme 3A). Interestingly, the decarboxylative addition reaction of proline reacts in a regioselective manor when reacted with E-1,2bisboraneyl-1-silane [24] (7ak), yielding a rapid access to the γamino 1,2-bisboryl-1-silane product (6ak), which passes through a boron-silicon-stabilized radical intermediate [25] (III-ak) (Scheme 3B). This radical has an SRE of xx Kcal/mol.…”
mentioning
confidence: 99%